Mortality factors associated with COVID-19 in the Central Highlands of Peru: Huánuco, 2020-2021 - Palma-Lozano, Diana (2024)
Objective: To determine the factors associated with COVID-19 mortality in the Central Highlands of Peru, specifically in the Department of Huánuco during 2020-2021. Methods: This quantitative, observational, analytical, and retrospective study collected medical records from 903 patients treated at the Amarilis Temporary Care and Isolation Center (CAAT, by its Spanish acronym) of the Hospital Materno Infantil (HMI) Carlos Showing Ferrari in Huánuco, Peru. The inferential analysis involved a bivariate logistic regression model and a multivariate predictive model to associate various factors with COVID-19 mortality. Results: The predictive logistic regression model identifed a COVID-19 mortality rate of 8.19% (74 patients). Factors significantly associated with increased mortality included advanced age (OR = 3.24; CI = 1.83 – 5.75), minimum oxygen saturation at admission (OR = 4.25; CI = 1.79 – 10.10), hypertension (OR = 2.01; CI = 1.17 - 3.45), sepsis during hospitalization (OR = 1.97; CI = 1.09 – 3.55), and male gender (OR = 1.77; CI = 1.03 – 3.04). Conclusion: Factors associated with increased COVID-19 mortality in the Central Highlands of Peru include advanced age, low oxygen saturation at admission, sepsis during hospitalization, and male gender